THE ROLE OF CUSTOMER SATISFACTION IN MODERATING INFLUENCE PRODUCT, PRICE AND PROMOTION TO PURCHASE DECISION LUXURY HOME IN MADIUN CITY (Case Study Customer of PT. Hanie Kurnian Jaya) - kurniawan, ihda (Universitas Slamet Riyadi, 2020)
PT. Hanie Kurnia Jaya is a Properties Developer that is located in Madiun City, East of Java. The problem of the research are the impact of product’s quality, price, promotion and customer satisfaction to the purchase decision and how customer satisfaction can moderate the quality of the product, price and promotion to purchase decision. The purpose of this research to give PT. Hanie Kurnia Jaya recommendation to increase their revenue and to become a reference for there other researchers. The method of this research are questionnaires that are given to customers of PT. Hanie Kurnia Jaya. The technique of data analisys of the research is multiple linear regression analisys , T-test, F-test, coefficient determination and absolute deviation. The result os this research shows that the product quality does not affect significantly on purchase decision of the customers, the price affects significantly on purchase decision of the customers, promotion affect significantly on purchase decision of the customers, customers satisfaction affect significantly on puechase decision of the customers, customers satisfaction does not moderate the affect of product quality on puechase decision of the customers and cutomers satisfaction moderate the affect of promotion on purchase decision of the customers in PT. Hanie Kurnia Jaya.